(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
In this research to the modified dynamics of Bogdanov’s map studied, and the found sensitivity to the initial conditions of the modified map found as well as the Lyapunov exponent .the general characteristics of the map by the diffeomorpism. Finally we boosted my research with matlab to find chaotic areas